The Evolving Security Policy of Japan and The Adherence to Antimilitarism Culture - Anindya, Chaula Rininta (UI Scholars Hub, 2016)
Japan has reinterpreted Article 9 as the fundamental constitution of their antimilitarist culture and shows its willingness to play a more active role in the International security. This article seeks to examine the changes of Japan’s security and the potential shift of antimilitarist strategic culture, arguing that despite the continuous changes, Japan has not changed its strategic culture due to perpetual debates within the domestic politics that are vital in shaping the security identity. The changing security practices are merely a natural response to the current dynamic of International security environments. Therefore, it remains unlikely for Prime Minister Shinzo Abe to achieve his aim for a constitutional reform.